Re-Constructing the Self in Language and Narrative in Eva Hoffman’s Lost in Translation: a Life in a New Language and Anaїs Nin’s Early Diaries - Jarczok, Anita (Studia Anglica Posnaniensia, 2016)
This essay analyses the life narratives of two European women - Anaїs Nin’s Diary and Eva Hoffman’s Lost in Translation - in order to investigate how their transition to North America affected their sense of self. It emphasises the key role that language and narrative play in the formation of identity, and argues that both writers reinvented themselves both in their adopted language and in writing.